2019
DOI: 10.3390/ijerph16132443
|View full text |Cite
|
Sign up to set email alerts
|

The New Path to Improve Construction Safety Performance in China: An Evolutionary Game Theoretic Approach

Abstract: Evidence shows that there are many work-related accidents and injuries happening in construction projects and governments have taken a series of administrative measures to reduce casualties in recent years. However, traditional approaches have reached a bottleneck due to ignoring market forces, and thus new measures should be conducted. This study develops a perspective of safety performance (SP) for construction projects in China and puts forward a conception of the safety information system by using several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 59 publications
1
35
0
Order By: Relevance
“…Some of the employees are only productive when their managers closely supervise them. The absence of the latter implies that a significant portion of the juniors would delay meeting their deadlines, which is a factor likely to impact the realization of the desired deliverables (Gao, Chen, & Liu, 2019). According to the authors, the employees who keep a distance from their junior contractors are likely to experience delays since their absence allows the followers to engage in less productive activities that are not related to the construction work.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the employees are only productive when their managers closely supervise them. The absence of the latter implies that a significant portion of the juniors would delay meeting their deadlines, which is a factor likely to impact the realization of the desired deliverables (Gao, Chen, & Liu, 2019). According to the authors, the employees who keep a distance from their junior contractors are likely to experience delays since their absence allows the followers to engage in less productive activities that are not related to the construction work.…”
Section: Discussionmentioning
confidence: 99%
“…According to the aforementioned four strategies, after an information exchange, an evacuated subject with limited rationality would re-evaluate the payoff and adopt the decision-making behavior of whether to evacuate, which means the subjects ate supposed to learn how to play through experience [39]. After a single game, the subject would not withdraw from the social group.…”
Section: Evacuate Staymentioning
confidence: 99%
“…Given the safety production behavior and its regulatory characteristics of industrial cluster enterprises, Liu et al [45] revealed the evolution law of enterprise safety production behavior selection through the evolution model analysis of the interaction process between government regulation agencies and enterprises. Pi [46] developed a perspective of safety performance (SP) for construction projects in China and put forward a conception of the safety information system to strengthen the safety supervision of participants in the construction industry. However, none of the above studies considered the influence of third-party regulation service agencies, nor did they consider the issue of power rent-seeking between third-party regulation service agencies and chemical enterprises, which is a prerequisite for better playing the role of a third party in the safety regulation process of chemical enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%